Coherence of the EU cohesion policy and national regional policy: the case of the Czech Republic - Jiøí Novosák (European Regional Science Association (ERSA), 2014)
There is a high research and political interest in regional disparities now. Regional disparities are at the heart of prominent theories of regional development as well as of the ambitious project of European integration. Moreover, regional policies at various spatial levels are formulated in order to reduce the problems arising from large regional disparities. However, the multi-level character of regional policies evokes the question of their coherence. It is noteworthy that such a question is frequently mentioned in scholar literature but with limited empirical evidences. The intent of this paper is to contribute to the discussion on the coherence of regional policies, using the Czech Republic as a case study. The EU cohesion policy has become the dominant source of funding for regional development in the Czech Republic after its accession to the European Union in 2004. In addition, there is a national regional policy in the Czech Republic which defines the so called regions with concentrated state aid at the district level. The goal of this paper is to assess the spatial coherence of these two policies. In other words, the regional pattern of the EU cohesion policy expenditures in the programming period 2007-2013 in the Czech Republic is mapped considering the position of the regions with concentrated state aid. Besides the overall assessment, the spatial pattern of the EU cohesion policy expenditures is decomposed thematically as well. The assessment is based on the database of more than forty-six thousand projects which were co-financed from the EU cohesion policy. The main findings of the research point at ambivalent spatial coherence of the EU cohesion policy on one hand and Czech national regional policy on the other. Thus, there is not a relatively higher allocation of the EU cohesion policy expenditures in the regions with concentrated state aid. This is true also for thematic decomposition, and especially for more progressive themes such as R&D, innovation and new technologies. Altogether, the findings suggest that additional measurements are necessary in order to increase the spatial coherence of the policies. Some suggestions related to the territorially based instruments of the EU cohesion policy for the programming period 2014-2020 are given.
Keywords: R12; R58; O18; O22; 330; regional policy; EU cohesion policy; coherence of regional policies; Czech Republic